A Legendary Polynomial Approach to Solutions of Volterra Integro-Differential Equations with Delay - Raji, M. T.; Olajuwon, B. I. (Academy Journal of Science and Engineering)
This paper presents a numerical computation approach to the solution of Volterra Integro-Differential Equation with delay via legendary Polynomial method. Computational code was developed and implemented on a Mathematical Software (Matlab 2009b) to solve the problem. The accuracy, efficiency and effectiveness of the method of solution were ascertained by comparing the solution obtained with the exact solution in the literature and it showed that the present results were in agreement with both the exact and existing results.